The ineffectiveness of nasal dilator strips under aerobic exercise and recovery conditions - Baker, K. M.; Behm, D. G. (The Journal of Strength and Conditioning Research, 1999)
Nasal dilator strips (NDSs) are purported to improve athletic performance by decreasing nasal airway resistance. The purpose of this investigation was to determine the effects of NDSs on cardiorespiratory function, work output, and perceived exertion under resting, submaximal and maximal exercise, and recovery conditions. Ten subjects were blinded to the purpose of the study by disguising the strips under white adhesive tape. Using a random selection process, subjects performed 2 stepwise progression (0.5 W) bicycle ergometer tests to exhaustion wearing either an NDS or a suture strip. Cardiorespiratory data, including aerobic capacity (o2), ventilatory volume and rate, respiratory quotient, heart rate, blood pressure, and thoracic volume changes were monitored using a face mask apparatus. Perceived exertion was monitored using Borg`s scale. Data were analyzed using a 2-way repeated-measures analysis of variance (p < 0.05) and the Pearson product moment correlation for reliability. No significant differences were found between testing conditions for any of the measurements, including time to exhaustion. High test-retest reliability coefficients (0.8-0.98) for all measurements exemplified the null effect of the NDSs. Thus, NDSs proved to be ineffective in improving cardiorespiratory function, work output, and perceived exertion under all testing conditions.